English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I've taken the logs:
log y = log 1 - log (x-a)(x-b)
so
log y = -log(x-a)(x-b)
so
log y = -log(x-a) - log(x-b)
not sure if this is correct so far, if yes, still can't see how it fits into y =mx+c
Please help!!!

2006-12-10 08:45:55 · 3 answers · asked by andrew p 1 in Science & Mathematics Mathematics

3 answers

y = 1/(x-a)(x-b)
y = 1/(x^2 - bx - ax + ab)
y = 1/(x^2 - (a+b)x + ab)

This equation cannot be reduced to a linear equation as it is not linear. The denominator consists of a quadratic equation and it is also a reciprocal.

2006-12-10 08:56:18 · answer #1 · answered by Kemmy 6 · 1 1

You won't be able to reduce this equation to y=mx+b, because the equation is not linear, it's quadratic.

2006-12-10 16:56:30 · answer #2 · answered by SIMON G 1 · 0 1

Until here it is correct:

log y = log 1 - log (x-a)(x-b)
so
log y = -log(x-a)(x-b)
so
log y = -log(x-a) - log(x-b)

But here is the final reduction possible!!!

2006-12-11 04:43:36 · answer #3 · answered by Escatopholes 7 · 0 0

fedest.com, questions and answers